2012
DOI: 10.1186/1471-2407-12-459
|View full text |Cite
|
Sign up to set email alerts
|

Loss of aquaporin 3 protein expression constitutes an independent prognostic factor for progression-free survival: an immunohistochemical study on stage pT1 urothelial bladder cancer

Abstract: BackgroundTreatment of patients with stage pT1 urothelial bladder cancer (UBC) continues to be a challenge due to its unpredictable clinical course. Reliable molecular markers that help to determine appropriate individual treatment are still lacking. Loss of aquaporin (AQP) 3 protein expression has previously been shown in muscle-invasive UBC. The aim of the present study was to investigate the prognostic value of AQP3 protein expression with regard to the prognosis of stage pT1 UBC.MethodAQP 3 protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…Although the expression of AQP3 was not associated with survival of colon cancer in the current study, several studies have reported on the prognostic significance of AQPs in solid tumors [12,24,25]. For example, human epidermal growth factor increased the expression of AQP3 and enhanced the migration ability of a human colorectal cancer cell line in an in vitro study.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Although the expression of AQP3 was not associated with survival of colon cancer in the current study, several studies have reported on the prognostic significance of AQPs in solid tumors [12,24,25]. For example, human epidermal growth factor increased the expression of AQP3 and enhanced the migration ability of a human colorectal cancer cell line in an in vitro study.…”
Section: Discussioncontrasting
confidence: 60%
“…However, Pei et al [24 ]reported that the expression of AQP3 was not increased in colorectal cancer when compared to normal or adenoma tissues. More recently, loss of AQP3 expression has been reported to be associated with worse survival in patients with bladder cancer, where the authors suggested that dysregulation of AQP3 may be part of a molecular program associated with progression to bladder cancer [25]. Consequently, these results show that the role of AQP3 still requires further clarification.…”
Section: Discussionmentioning
confidence: 93%
“…We concluded that AQPs may play a role in the progression of UBC and, in particular, that this could be of prognostic value 5 . In support of this, we have recently demonstrated that loss of AQP3 protein expression was an independent marker associated with worse progression-free survival in patients with pT1 UBC, a finding that was confirmed by multivariate Cox regression analysis 6 .…”
Section: Introductionsupporting
confidence: 56%
“…In support of this, we have provided strong presumptive evidence that loss of AQP3 protein expression is associated with worse progression-free survival in patients with pT1G2/G3 carcinomas and we hypothesized that this could also apply to muscle-invasive tumours 6 . This hypothesis seems to be confirmed by the results of the present study.…”
Section: Discussionmentioning
confidence: 73%
“…Li et al [24] reported that AQP3 overexpression could facilitate colorectal carcinoma cell migration and that AQP3 may be considered a potential indicator and therapeutic target for colon tumor metastasis and prognosis. Otto et al [25] indicated that loss of AQP3 protein expression in pT1 bladder cancer may play a key role in disease progression and is associated with worse progression-free survival. In this study, we also found that the overexpression of both AQP3 and AQP5 was associated with advanced tumor stage, positive distant metastasis, and unfavorable prognosis.…”
Section: Discussionmentioning
confidence: 99%